In vitro clonal propagation of Phalaenopsis using floral nodes - Fadriquela, Liza F. (2000)
This study has two parts, the establishment of sterilization procedure and the node culture stage. In the sterilization stage, nodes were subjected to different concentrations of Clorox (5.25% Na hypochlorite) at different time intervals. Data obtained showed that 15% Clorox for 30 min and 20% Clorox for 15 to 30 min were effective in reducing the contamination rate. In the node culture stage, floral nodes of young floral stalks were inoculated in Vacin and Went medium to develop initial protocols for in vitro culture techniques of Phalaenopsis and to determine which node locations successfully produce shoots. Node locations 1 to 5 were able to produce shoots. The highest average length of shoots was obtained from node location 3. Statistical analysis showed the nodes 1, 2 and 5 were significantly different from nodes 3 and 4 at 5% level of significance in terms of shoot production
Thesis (BS Biology) -- University of the Philippines Mindanao, 2000